Design of Special Adapters and Furnace for Hot Helium Leak Testing of Plasma Physics Components. (2017) - Govindaraju, M.; Ananthakrishnan, R.; Khan, Nida; Magar, Mayur; Nayakwade, Chetan; Bardepur, Rakesh; Balasubramanian, K
Abstract: Pressure and leak testing are the two most important quality control steps followed at the end of fabrication for the components of ITER, Plasma physics and its related fields. In the current project, an elaborate procedure and facilities for the hot helium leak testing has been established. A conventional vacuum furnace has been modified to accommodate the global leak testing of high technology Plasma physics and ITER components. Special adaptors were designed and fabricated for hot helium leak testing under pressure mode. These adapters have a transfer tube which can be used to carry the helium in and out of the component under testing, without disturbing the vacuum level in the furnace chamber. These adapters were fitted to the 2000 mm long ITER components and tested successfully at the operating temperature of 200 °C. High end vacuum fittings and sealing mechanisms were installed on the mating surfaces of the furnace, to achieve high vacuum in the order of 10 -5 mbar. Provisions have been given to address the challenge of local leak detection by installing a Wilson seal to move from one end of the component to other end; in such a way that one side of the seal is at 200 °C temperature in vacuum, other side is at room temperature in atmospheric pressure. This enables to locate the leak by moving the component form one end to other.